Augmented epigenetic repression of hepatitis B virus covalently closed circular DNA by interferon-α and small-interfering RNA synergy - Kongying Hu; Wenjing Zai; Mingzhu Xu; Haiyu Wang; Xinluo Song; Chao Huang; Jiangxia Liu; Juan Chen; Qiang Deng; Zhenghong Yuan; Jieliang Chen (mBio, 2024)
ABSTRACT The persistence of hepatitis B virus (HBV) covalently closed circular DNA (cccDNA) is a key obstacle for HBV cure. This study aims to comprehensively assess the effect of interferon (IFN) and small-interfering RNA (siRNA) combination on the cccDNA minichromosome. Utilizing both cell and mouse cccDNA models, we compared the inhibitory effects of IFNα, siRNA, and their combination on cccDNA activity and assessed its epigenetic state. IFNα2 treatment alone reduced HBV RNAs, HBeAg, and HBsAg levels by approximately 50%, accompanied by a low-level reconstitution of SMC5/6—a chromatin modulator that restricts cccDNA transcription. HBx-targeting siRNA (siHBx) achieved significant suppression of viral antigens and reconstitution of SMC5/6, but this effect could be reversed by the deacetylase inhibitor Belinostat. The combination of IFN with siHBx resulted in over 95% suppression of virological markers, reduction in epigenetic activation modifications (H3Ac and H4Ac) on cccDNA, and further reduced cccDNA accessibility, with the effect not reversible by Belinostat. In an extracellular humanized IFNAR C57BL/6 mouse model harboring recombinant cccDNA, the effect of combination of clinically used pegylated IFNα2 and GalNac-siHBx was further clarified, indicating a higher and more durable suppression of cccDNA activity compared to either therapy alone. In conclusion, the combination of IFNα and siRNA achieves a more potent and durable epigenetic inhibition of cccDNA activity in cell and mouse models, compared to monotherapy. These findings deepen the understanding of cccDNA modulation and strengthen the scientific basis for the potential of combination therapy.IMPORTANCESince there are currently no approved drugs targeting and silencing covalently closed circular DNA (cccDNA), achieving a “functional cure” remains difficult. This study aims to comprehensively compare the effects of IFNα, small-interfering RNA targeting hepatitis B virus (HBV), and their combination on the activity, accessibility, and epigenetic modifications of cccDNA minichromosomes in cell models. A more durable and stable inhibition of HBV RNAs and antigens expression by IFNα and HBx-targeting siRNA (siHBx) synergy was observed, associated with augmented epigenetic repression of the cccDNA minichromosome. Besides, in an extracellular humanized IFNAR mouse model harboring recombinant cccDNA with an intact response to human IFNα, the synergistic effect of clinically used pegylated IFNα2 and in-house-developed GalNac-siHBx was further clarified.